Prediction of Shear Lag Effect in Thin-Walled Single-Box Multicell Box Girder Based on the Modified Warping Displacement Function - Xiayuan Li; Shui Wan; Kongjian Shen; Peng Zhou; Xiao Wang (Advances in Civil Engineering)
In this study, an effective and accurate theoretical analysis method for predicting the shear lag effect in the thin-walled single-box multicell box girder is presented. The modifications of longitudinal warping displacement functions at the flanges are fully investigated, including the shear lag width (bij) of flanges, the coefficients (αij) of shear lag warping functions, the deformation compatibility conditions in flanges, and the internal force balance (D). The initial shear deformation (γ03) in the top lateral cantilever flanges is innovatively introduced in multicell box girders and obtained by the designed procedure. In addition, the transverse distribution function for describing the longitudinal warping displacement is deduced and expressed in the form of the cosine function. Based on the principle of minimum potential energy, the governing differential equations are derived and solved with the associated boundary and load conditions. The accuracy and applicability of the proposed method (SL-THY2) are validated for four thin-walled single-box multicell (two- and three-cell) box girders with the results derived from the solid finite element method.